169 P53 Deficiency Prevents oxygen-induced MESENCHYMAL THICKENING IN mice. (1st January 2006) - O'Brien, E.; Zhao, L.; Yu, X.; Hale, M.; McKnight, R. A.; Albertine, K. A.; Lane, R. H.
Abstract : Background: Uteroplacental insufficiency in humans is a common prenatal insult that leads to intrauterine growth restriction (IUGR), prolonged need for supplemental oxygen, and a predisposition toward dysregulated alveolar formation. Dysregulation of alveolar formation is manifest morphologically by thickened mesenchyme. Using our rat model of uteroplacental insufficiency-induced IUGR, we have previously presented that IUGR increases both perinatal and postnatal pulmonary p53 gene expression in association with dysregulated alveolar formation. p53 is a well studied transcription factor that regulates apoptosis and cell cycle regulation, key processes in alveolar formation. Objective: With the objective of demonstrating that p53 plays a pivotal role in the dysregulation of alveolar formation, we hypothesized that p53 deficiency blunts the developing lungs' response to hyperoxic stress. Methods: To test this hypothesis, we used the transgenic mice that are p53 deficiency: (C.129S2(B6)-Trp53 tm1Tyj/j ). To determine if p53 mRNA expression is different in the lungs of p53 transgenic mice, real-time RT-PCR was performed on p53 +/+, +/-, and -/- mouse lungs. In order to evaluate oxygen-induced changes lung histology and morphometry in a developing mouse lung in a p53 dose-dependent manner, p53 transgenic mice (+/+, +/-, -/-) and their dams were exposed to 60% oxygen from DOL 3 to DOL 6, corresponding to initiation of alveolar formation. Lungs were isolated at DOL 21, and morphometric analysis was performed to assess the extent of oxygen-induced alveolar dysregulation ( n = 3 litters). Results: We found that p53 -/- lungs contained 3% of the p53 mRNA contained in +/+ lungs, and that p53 +/- lungs contained 41% of the p53 mRNA contained in the +/+ lungs. 60% oxygen increased mesenchyme thickness of the +/- p53 mice (1.70 ± 0.10 μm), whereas the p53 deficiency resulted in a significant decrease in mesenchyme thickness (1.55 ± 0.11* μm; p < .05). Conclusion: We have previously demonstrated that IUGR affects epigenetic characteristics of the p53 gene and causes a persistent increase in p53 gene expression in the IUGR model of dysregulated alveolar formation. We now find that lack of p53 protects the developing lung from oxygen-induced mesenchymal thickening in these transgenic mice. We speculate that p53 plays a pivotal role in the developing lung's response to stress. University of Utah CHRC and the CHRCDA.